Frequency of Iron Deficiency Anemia in Young Females with Migraine - Rashid, Samina; Haq Nawaz, Khurram; Athar, Muhammad Hammad; Fakhar, Amar; Hakeem, Farzana; Manzoor, Namra (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the frequency of iron deficiency anaemia among young female migraine patients and look for the factors related to the presence of anaemia.Study Design: Cross-sectional study.Place and Duration of Study: Department of Medicine, Pak Emirates Military Hospital, Rawalpindi Pakistan, from Sep 2018 to Feb 2019.Methodology: One hundred and thirty young female patients with migraine presenting at our hospital were enrolled in this study. Diagnosis of Migraine was established by the consultant neuro physician based on the International Classification of Headache Disorders diagnostic criteria for migraine. Iron deficiency anaemia was diagnosed based on haemoglobin and ferritin levels. Various social and demographic factors were studied in this study, along with iron deficiency anaemia among the young females suffering from migraine.Results: Out of 130 young female patients with migraine, 69 (53.1%) showed the presence of iron deficiency anaemia, while 61 (46.9%) had no anaemia. Upon statistical analysis, it was revealed that menstrual abnormalities had a statistically significant association with the presence of iron deficiency anaemia among the young female patients with migraine.Conclusion: Iron deficiency anaemia was the common finding among young female patients with migraine in Pakistan. Menstrual abnormalities among these young female migraine patients were related to the presence of iron deficiency anaemia. A detailed history of menstrual abnormalities and anaemia screening among migraine patients may be helpful for early diagnosis and intervention.